Nilai Profetik Dalam Novel 99 Cahaya Di Langit Eropa Karya Hanum Salsabiela Dan Rangga Almahendra: Kajian Semiotik Dan Relevansinya Dalam Pembelajaran Sastra Indonesia Di Sma - Ferdiansyah, .Ferdiansyah; , Prof. Dr. Ali Imron Al-Ma'ruf, M.Hum; , Dr. Nafron Hasyim (2016)
The purpose of this study consisted of (1) to describe the background of the socio-cultural authors Hanum Salsabiela and Rangga Almahendra, (2) describe the structure of the novel 99 Cahaya Langit di Eropa works Hanum Salsabiela and Rangga Almahendra, (3) describe the prophetic value in novel 99 Cahaya Langit di Eropa works and Rangga Almahendra Salsabiela Hanum (4) describes the value relevance prophetic relevance in learning Indonesian literature at the high school. This study is qualitative descriptive with fixed strategy. The data used in this study in the form of words, sentences, and paragraphs. Source of research data such as documents, namely the novel text 99 Light in the Sky Europe works Hanum Salsabila and Rangga Almahendra, and books on literature relevan.Teknik data collection using the techniques of literature, see, and record. Analysis technique using a method of reading the semiotic models, such as heuristic and hermeneutic reading. The results of this study were (1) In the socio-historical, works Hanum and Rangga bernuansakan spritual by making Europe as an object of study, (2) Review of the structure of the novel 99 Cahaya Langit di Eropa emphasizes the theme and the facts of the story, (3) Value prophetic produce (a) Amar ma'ruf (humanization), (b) Nahi munkar (liberation) (c) Tu'minuna billah (transcendence), (4) Relevance prophetic value to learning Indonesian literature in high school can be seen from the standard of competence stipulated in the form of an attitude (attitude) is the same with education and humanities, skills (skills) together with education and humanities, and knowledge (knowledge) is the same with education humanum